Percy Cochrane collection - Cochrane, Percy, 1907-1980. (1949)
Series of recordings of the customs and music of Papua New Guinea and Gilbert & Ellice Islands.
Digital master available
Uncorrected transcript (typescript, 109 leaves) available.
Keywords: Papua New Guinean people -- Songs and music; Rites and ceremonies -- Papua New Guinea; Rites and ceremonies -- Gilbert and Ellice Islands Colony; Papua New Guinea -- Songs and music; Gilbert and Ellice Islands Colony -- Songs and music